C-erbB-2 immunostaining: problems with interpretation. Issue 9 (September 1994) - Kay, E W; Walsh, C J; Cassidy, M; Curran, B; Leader, M
Abstract : AIMS--To assess the consistency and reproducibility of assessment of c-erbB-2 immunostaining, and to examine some of the problems relating to inter- and intraobserver variability in the documentation of positive staining; to profile the spectrum of cytoplasmic and membranous staining in a wide range of tumour types. METHODS--A total of 283 neoplasms were examined for immunohistochemical expression of the c-erbB-2 oncoprotein. Three independent observers were required to assess intensity both of membrane and cytoplasmic staining on a three point and then a four point scale. Extent of positive staining was also assessed on a two point scale. A minimum of two weeks elapsed between assessments using the differing scales. RESULTS--Positive membrane staining was documented by one or more observers in 16.6% of tumours examined. This positivity was largely restricted to bladder, renal, and breast tumours. The overall level of disagreement as to the presence or absence of membranous staining was 11.3%. Cytoplasmic staining was identified in 55.5% of tumours studied. The level of disagreement as to the presence or absence of cytoplasmic staining was 26.5%. CONCLUSIONS--Intraobserver variability was minimal, indicating that each pathologist was adhering to internal reproducible standards. Interobserver variability was greater, indicating that the interpretation of c-erbB-2 immunostaining may require set guidelines. It is suggested that assessment should be referenced to a standard positive control, that a three tier system for grading of intensity and a two tier system for grading of extent should be adopted, and that the evaluation should be agreed by at least two pathologists. The presence of cytoplasmic staining should continue to be routinely recorded until its biological role and clinical implications are fully understood.